2021
DOI: 10.1159/000513079
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Survival and Survival without Major Morbidity in Very Preterm Infants in Two Neonatal Networks: SEN1500 and NEOCOSUR

Abstract: Introduction: Very low-birth weight (VLBW) infants represent a high-risk population for morbidity and mortality in the neonatal period. Variability in practices and outcomes between centers has been acknowledged. Multicenter benchmarking studies are useful to detect areas of improvement and constitute an interesting research tool. Objectives: The aim of the study was to determine the perinatal variables and interventions associated with survival and survival without major morbidity in VLBW infants and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Studies have shown that ELBW is associated with significantly high mortality with survival decreasing as gestational age reduced. [20][21][22][23][24][25] After controlling for the effect of gestational age and birth weight on survival, our study demonstrated a 74% reduction in the odds of mortality in preterms delivered <1500g in the post-bCPAP era. This is in contrast to a study in Kenya where, following bCPAP implementation, survival to discharge improved from 61% to 85%.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Studies have shown that ELBW is associated with significantly high mortality with survival decreasing as gestational age reduced. [20][21][22][23][24][25] After controlling for the effect of gestational age and birth weight on survival, our study demonstrated a 74% reduction in the odds of mortality in preterms delivered <1500g in the post-bCPAP era. This is in contrast to a study in Kenya where, following bCPAP implementation, survival to discharge improved from 61% to 85%.…”
Section: Discussionmentioning
confidence: 62%
“…Studies have shown that ELBW is associated with significantly high mortality with survival decreasing as gestational age reduced. 2025…”
Section: Discussionmentioning
confidence: 99%
“…Male neonates had 1.43 higher hazards of mortality compared to females; which is contradictory to a finding of a study in Spain. 40 Preterm neonates having fifth minute Apgar score <7 had almost two times higher hazards of death compared to those having ≥7, which is supported by studies in Spain and Rwanda. 40,41 Furthermore, compared to their counterparts, preterm neonates with birth asphyxia had twice the risk of dying; which is supported by studies in Uganda and Nigeria.…”
Section: Discussionmentioning
confidence: 67%
“…Preterm neonates having fifth minute Apgar score <7 had almost two times higher hazards of death compared to those having ≥7, which is supported by studies in Spain and Rwanda. 40, 41 Furthermore, compared to their counterparts, preterm neonates with birth asphyxia had twice the risk of dying; which is supported by studies in Uganda and Nigeria. 37, 39 This might be due to oxygen deficit during delivery leading to severe hypoxia of vital organs and becoming a double burden, which is an implication for close labor follow-up.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation